Low 5-hydroxymethylcytosine level is an independent predictor of high histological grade in locally advanced breast cancer. Issue 1 (2020) - Prada, Diddier; Díaz-Chávez, José; Peña-Curiel, Omar; Ramírez, Miguel; Colicino, Elena; Villarreal-Garza, Cynthia
No abstract available